The Influence of Leadership, Organizational Culture, and Work Environment on Organizational Citizenship Behavior (OCB) at PDAM Tirta Giri Nata, Cirebon City - Putri Ayu Widiasari; Uwis Sriwulandari; Ade Solahudin; Sunimah Sunimah (Interdisciplinary Social Studies, 2025)
This study examines the influence of leadership, organizational culture, and work environment on Organizational Citizenship Behavior (OCB) at PDAM Tirta Giri Nata, Cirebon City. Using the purposive sampling method, this study selected participants based on certain criteria. Primary data were collected through questionnaires, and data analysis was carried out using validity and reliability tests, as well as multiple regression analysis with SPSS version 20. The findings of the study show that leadership and organizational culture have no significant effect on OCB, while the work environment has a positive influence. This study was limited by a sample of 89 employees out of 224 employees, because data collection was carried out at the end of the year when company activity was high, and many employees were doing external assignments. In addition, this study only focuses on PDAM Tirta Giri Nata Cirebon City, which may limit the generalization of research results. Further research should explore the contexts of other organizations to improve their implementation. This study contributes to the existing literature by examining the combined effects of leadership, organizational culture, and work environment on OCB in the context of public utility companies.